The Qur’anic Concept of Mīthāq in the Critique of Modernity: A Comparative Study of Al-Attas and Taha Abdurrahman - Agustono, Ihwan; Arroisi, Jarman; Zain, Naura Safira Salsabila (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
Modernity is a fundamental issue in contemporary Islamic thought, particularly due to its secular and rationalist nature that stands in contrast to the metaphysical foundations of Islam. Originating from Western post-Renaissance civilisation, modernity introduces a worldview that marginalises transcendent values and promotes the separation between religion and public life. This article aims to comparatively analyse the critical responses of two prominent Muslim thinkers, Syed Muhammad Naquib al-Attas and Taha Abdurrahman, to Western modernity, with particular emphasis on the concept of mīthāq (primordial covenant) as an ontological and ethical foundation for Islamic civilisation. Employing a qualitative method and discourse analysis of their primary texts, this study finds that although both scholars agree on the metaphysical disorientation of modernity and its consequences for moral and epistemological crises, they differ in their approaches. Abdurrahman proposes an ethical paradigm rooted in qalb, while al-Attas advocates for the Islamisation of knowledge based on revelation. Both thinkers ground their critiques in the awareness of mīthāq as a spiritual bond between human beings and God, which forms the basis for ethics, knowledge, and social order in Islam. Thus, their critiques of modernity are not merely socio-political but constitute a metaphysical reconstruction that reorients human responsibility toward the divine order.